Blood Lactate AUC Is a Sensitive Test for Evaluating the Effect of Exercise Training on Functional Work Capacity in Patients with Chronic Heart Failure. (30th September 2021) - Valborgland, Torstein; Isaksen, Kjetil; Munk, Peter Scott; Larsen, Alf Inge
Abstract : Purpose . Exercise training is an essential treatment option for patients with chronic heart failure (CHF). However, it remains controversial, which surrogate measures of functional work capacity are most reliable. The purpose of this paper was to compare functional capacity work measured as capillary lactate concentrations area under the curve (AUC) with standard cardiopulmonary exercise testing (CPET) with VO2peak and the 6-minute walk test (6 MWT). Methods . Twenty-three patients in New York Heart Association (NYHA) class II/III with left ventricular ejection fraction (LVEF) <35% were randomised to home-based recommendation of regular exercise (RRE) (controls), moderate continuous training (MCT) or aerobic interval training (AIT). The MCT and AIT groups underwent 12 weeks of supervised exercise training. Exercise testing was performed as standard CPET treadmill test with analysis of VO2peak, the 6 MWT and a novel 30-minute submaximal treadmill test with capillary lactate AUC. Results . All patients had statistically significant improvements in VO2peak, 6 MWT and lactate AUC after 12 weeks of exercise training: 6 MWT (p =0.035), VO2peak (p =0.049) and lactate AUC (p =0.002). Lactate AUC (p =0.046) and 6MWT (p =0.035), but not VO2peak revealed difference between the exercise modalities regarding functional work capacity. Conclusion . 6-MWT and lactate AUC, but not VO2peak, were able to reveal a statistically significant improvement in functional capacity between different exercise modalities.